Influencia de la Corte Interamericana en el concepto de reparación integral para la consecución de la justicia en materia contencioso administrativa (2016)
The text begins with the explanation of the scope it has for the Court the right to free access to the administration of justice in the light of Articles 8.1, 25 and 63 of the American Convention on Human Rights, ratified by Colombia and inserted into the domestic law from constitutional block, and then analyze the relationship of this right to full compensation from the cases decided by the Court in which Colombia was convicted even having paid compensation under domestic law. In conclusion, the causes that led to ignorance of the Court, on the rulings of the administrative jurisdiction, as a form of justice will be addressed.